2011
DOI: 10.1371/journal.pone.0022828
|View full text |Cite
|
Sign up to set email alerts
|

The MicroRNA-200 Family Is Upregulated in Endometrial Carcinoma

Abstract: BackgroundMicroRNAs (miRNAs, miRs) are small non-coding RNAs that negatively regulate gene expression at the post-transcriptional level. MicroRNAs are dysregulated in cancer and may play essential roles in tumorigenesis. Additionally, miRNAs have been shown to have prognostic and diagnostic value in certain types of cancer. The objective of this study was to identify dysregulated miRNAs in endometrioid endometrial adenocarcinoma (EEC) and the precursor lesion, complex atypical hyperplasia (CAH).MethodologyWe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 38 publications
11
93
0
Order By: Relevance
“…[26][27][28][29][30] That might be due to different platform and normalization strategies used, as well as utilization of sample sets with various histological types, grade and clinical stage layouts. To reveal miRNA signatures characteristic exclusively for EEC, which is the most common type of endometrial malignancy, our study comprised cases with histologically proven endometrioid histology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[26][27][28][29][30] That might be due to different platform and normalization strategies used, as well as utilization of sample sets with various histological types, grade and clinical stage layouts. To reveal miRNA signatures characteristic exclusively for EEC, which is the most common type of endometrial malignancy, our study comprised cases with histologically proven endometrioid histology.…”
Section: Discussionmentioning
confidence: 99%
“…All miR-200 family members were significantly upregulated, which confirms results reported in few recently published studies. 26,29,30 Moreover, expression of those miRNAs was most pronounced in early clinical stages of EEC and a systematic decrease of their expression was noted in higher FIGO stages and in poorly differentiated tumors, which was significant in case of miR-200a, miR-200b* and miR-429. The role of miR-200 family (miR-141, miR-200a, miR-200b, miR-200c and miR-429) in EEC cancer has not been elucidated so far.…”
Section: Early Detection and Diagnosismentioning
confidence: 98%
See 1 more Smart Citation
“…A number of recent studies have investigated the expression profiles of miRNAs in endometrial cancer Cohn et al, 2010;Ratner et al, 2010;Snowdon et al, 2011). Several studies reported elevated expression level of miR-205 in different types of endometrial cancer compared to normal endometrial tissues and plasmas (Boren et al, 2008;Hiroki et al, 2010;Karaayvaz et al, 2012).…”
Section: Mir-205 In Endometrial Cancermentioning
confidence: 99%
“…Of the current data, the miR-200 family is the most well studied. Snowdon et al (2011) reported that miR-200a/ b/c, miR-141, and miR-429 were upregulated in both endometrioid endometrial adenocarcinoma and complex atypical hyperplasia compared with normal control endometrium. Subsequent studies (Lee et al 2011, Park et al 2012 Three additional studies have evaluated the potential role of miRNAs in modulation of tumor suppressor genes in the context of endometrial adenocarcinomas.…”
Section: Uterus: Endometriummentioning
confidence: 99%